Paradigm of solar energy in Brazil and the world - Kemerich, Pedro Daniel da Cunha; Flores, Carlos Eduardo Balestrin; Borba, Willian Fernando de; Silveira, Rafael Borth da; França, Jacson Rodrigues; Levandoski, Natalie (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
With the gradual increase of population and consumption patterns of today's society, debates involving energy issues are becoming more frequent. The energetic basis of Brazil revolves around the dams, since the country has a great water conditions. With the scarcity of non-renewable resources caused by rampant consumption, they turn their eyes to the renewable energy sources, chief among which is solar energy. Thus the present study aimed to list the situation, types, difficulties and expectations of solar energy in Brazil and worldwide. Was identified that the country has a potential grid for generating such energy, but still faces mainly on financial issues for its implementation, which indicates that the government should invest in the sector, which can solve many problems related to access to electricity in isolated communities in the country.